Paternalistic breaches of confidentiality in prison: mental health professionals' attitudes and justifications. Issue 6 (13th January 2015) - Elger, Bernice Simone; Handtke, Violet; Wangmo, Tenzin
Abstract : Aim: This manuscript presents mental health practitioners' (MHPs) practice, attitudes and justifications for breaching confidentiality when imprisoned patients disclose suicidal thoughts or abuse by others. Methods: 24 MHPs working in Swiss prisons shared their experiences regarding confidentiality practices. The data were analysed qualitatively and MHPs' attitudes and course of action were identified. Results: Analysis revealed paternalistic breaches of confidentiality. When patients reported suicidal thoughts and abuse, MHPs believed that forgoing confidentiality is necessary to protect patients, providing several justifications for it. Patients were informed that such information will be transmitted without their consent to medical and non-medical prison personnel. With reference to suicidal attempts, MHPs resorted to methods that may reduce suicidal attempts such as transfer to hospital or internal changes in living arrangements, which would require provision of certain information to prison guards. In cases of abuse, some MHPs convinced patients to accept intervention or sometimes overrode competent patients' refusals to report. Also in the case of abuse, provision of limited information to other prison personnel was seen as an acceptable method to protect patients from further harm. Discussion: Breaches of confidentiality, whether limited or full, remain unethical, when used for competent patients based solely on paternalistic justifications. Institutionalising ethical and legal procedures to address suicidal and abuse situations would be helpful. Education and training to help both medical and prison personnel to respond to such situations in an appropriate manner that ensures confidentiality and protects patients from suicide and abuse are necessary.